The conservation benefit of mowing vs grazing for management of species‐rich grasslands: a multi‐site, multi‐year field experiment. (2nd November 2015) - Tälle, Malin; Fogelfors, Håkan; Westerberg, Lars; Milberg, Per
Abstract : Species‐rich semi‐natural grasslands in Europe are becoming more fragmented and many species that depend on this habitat type are rare and threatened today. Management methods like mowing and grazing are needed to preserve remaining grasslands. Because management is costly it is important to use the most cost‐effective as well as the most beneficial management method, but few studies have compared mowing and grazing. We investigated the effect of mowing and grazing on grassland vegetation using data from 11 long‐term field trials situated in southern Sweden. We calculated the change in the odds of finding species belonging to three different groups of indicators at the start of the treatment and after 8 and 14 years. The used indicator groups were indicators of good management, excess nitrogen and poor management. The results revealed an increase in the odds of finding indicators of good management in mowed plots and an increase in finding indicators of excess nitrogen in grazed plots. The odds of finding indicators of poor management remained unchanged. Results from sub‐analysis of the grazing intensity showed a more negative effect from grazing with low grazing intensity than normal/high grazing intensity. Therefore, mowing is the best long‐term management method for semi‐natural grasslands in Sweden and grazing using a low grazing intensity should be avoided.